Addison's disease due to metastases to the adrenal glands. Issue 717 (July 1985) - Mor, F.; Lahav, M.; Kipper, E.; Wysenbeek, A. J.
Abstract : A 43 year old patient with Addison's disease secondary to extensive metastases to both adrenal glands is presented. Thirty two previously reported cases are reviewed; in only 13 cases was the diagnosis of Addison's disease confirmed biochemically. Reasons for the apparent rarity of Addison's disease in spite of the frequency of adrenal metastases are discussed. The need to consider the possibility of Addison's disease complicating known malignant disease arising in other tissues is stressed.